Nutritional Support and Clinical Outcome of Severe and Critical Patients With COVID-19 Pneumonia - Yue, Xiangfeng; Li, Min; Wang, Yu; Zhang, Jing; Wang, Xinyi; Kan, Linwei; Zhang, Xiaojian; Du, Shuzhang (Frontiers in Nutrition, 2020)
Background: In 2020, a novel coronavirus has spread throughout the world. More than four hundred thousand people died of 2019-nCOV pneumonia, most of which were severe and critical patients. No effective antiviral treatment has been verified thus far. Nutrition support has become one of the important means of treatment for severe and critical patients. Methods: In this retrospective, twenty-six severe patients and twenty-two critical patients with laboratory confirmed COVID-19 were enrolled in this study. We recorded diet and nutritional support in severe and critical patients. Baseline characteristics and clinical outcome of severe and critical patients were also collected. Results: Average calorie intake of severe patients (19.3kcal/kg/d) was higher than critical patients (15.3 kcal/kg/d) (P=0.04). Protein intake was similar in the two groups (0.65 g/kg per day and 0.62 g/kg per day, respectively; P=0.29). There was no significant difference in the median duration of viral shedding between the severe and critical patients (P=0.354). Conclusions: Compared with lower calorie intake, higher calorie intake could not improve duration of viral shedding with same protein intake. Therefore, if adequate calorie supply could not be achieved, permissive low calorie plus adequate protein intake is feasible for critical patients with 2019-nCOV pneumonia. Nevertheless, this evidence is not sufficient enough because of the small sample size. To show the real clinical benefit of permissive low calorie and adequate protein intake in severe 2019-nCOV pneumonia patients, a large and pragmatic randomized controlled trial is needed.